2007
DOI: 10.1007/s11262-007-0168-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of Banana bunchy top virus (BBTV) from Pakistan

Abstract: Banana bunchy top disease is caused by a single-stranded circular DNA virus, banana bunchy top virus (BBTV), which is a member of the genus Babuvirus (family Nanoviridae). We have cloned and sequenced five components (DNA-R, DNA-S, DNA-N, DNA-M and DNA-C) of a BBTV isolate originating from Pakistan. In addition, the DNA-R and several other components of five further isolates, originating from geographically distinct sites across the banana-growing area of Sindh province, Pakistan, were cloned and sequenced. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 23 publications
3
34
0
Order By: Relevance
“…BBTV isolates from India were found to be belonging to the PIO group [6,37,41]. Similarly, Amin et al [3] characterized the Pakistan (Sindh) isolate of BBTV by analyzing of sequences of DNA components and indicated that BBTV present in Pakistan belongs to the PIO group. The virus showed the highest levels of sequence identity to BBTV isolates originating from Egypt, India and Australia.…”
Section: Introductionmentioning
confidence: 98%
“…BBTV isolates from India were found to be belonging to the PIO group [6,37,41]. Similarly, Amin et al [3] characterized the Pakistan (Sindh) isolate of BBTV by analyzing of sequences of DNA components and indicated that BBTV present in Pakistan belongs to the PIO group. The virus showed the highest levels of sequence identity to BBTV isolates originating from Egypt, India and Australia.…”
Section: Introductionmentioning
confidence: 98%
“…In India, BBTV has been prevalent since 1943 and so it is possible that genetic variability such as that observed among isolates of the Asian group exists. Recently, the complete genomes of BBTV isolates occurring in Pakistan [1] and Lucknow, North India [19] were reported and found to belong to the South Pacific group.…”
Section: Introductionmentioning
confidence: 99%
“…1). BBTV is widely distributed in banana growing countries in the Asia, Pacific region (Australia, China, Guam, India, Pakistan, Sri Lanka, Hawaii, Indonesia, Japan, the Philippines, Taiwan, Tonga, Samoa and Vietnam) and in a few countries in Africa (Egypt, Gabon, Angola and Burundi) [2,16,50,89,99]. There are many other banana growing regions, South and Central America, the Caribbean, Papua New Guinea, Thailand and in many countries in African and Asia, where BBTV has not been confirmed [43,89].…”
Section: Geographical Distributionmentioning
confidence: 99%
“…The banana bunchy top disease was first observed of in Fiji in 1889. It emerged as a serious threat to banana cultivation in many countries, including Fiji in 1927, Egypt and India in 1953, the Philippines and Taiwan in 1961, Tonga and Samoa in 1967, China in 1979, Pakistan and Hawaii in 1989 [2,16]. In Australia, the banana industry in south-east Queensland and northern New Wales was virtually destroyed by the bunchy top disease in 1920 [16].…”
Section: Disease and Virus Descriptionmentioning
confidence: 99%
See 1 more Smart Citation